Best beach ever - Wax, Wendy (New York : Berkley, 2018)
"Forced to rent out or lose their beloved Bella Flora after the loss of their renovation-turned-reality-TV show Do Over, Maddie, Nikki, Avery, Kyra, and Bitsy move into cottages at the Sunshine Hotel and Beach Club , believing the worst is over...only to discover just how uncertain their futures really are. Maddie struggles with the challenges of dating a rock star whose career has come roaring back to life, while Nikki faces the daunting realities of mothering twins at forty-seven. Avery buries herself in a tiny home build in an attempt to dodge commitment issues, and Kyra battles to protect her son from the Hollywood world she once dreamed of joining. And Bitsy is about to find out whether the rewards of seeking revenge will outweigh the risks . Luckily, when the going gets tough, the ladies of Ten Beach Road know that their friendship--tried and tested--can chase away the darkest clouds and let the sunshine in"--
Includes a "Readers Guide" ([4] p.).
Keywords: Female friendship -- Fiction; Domestic fiction